(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
One of the main goals is to educate the developing young generation to be more educated and intelligent. In order to increase the interest of schoolchildren in Physics and their activity in solving problems, more convenient and new methods of solving problems are being developed. This article explains that in order to move an object along a horizontal line on an inclined plane, the direction of the resultant force must be horizontal, and the object always moves in the direction of the resultant force. In this, the projections of the forces acting on the body on the x and y axes were considered. To study the movement of a body that slides down an inclined plane with a height equal to H and stops at a certain distance on the horizontal plane, keeping the coefficient of friction constant during the entire movement. In this case, the length of the base of the inclined plane is equal to L and the total path traveled by the body is equal to S.